After Superficial Ablation for Superficial Reflux Associated with Primary Deep Axial Reflux, Can Variable Outcomes be Caused by Deep Venous Valve Anomalies?. (February 2017) - Maleti, O.; Lugli, M.; Perrin, M.
Abstract : Objective: To identify which deep anatomical anomalies can explain variable hemodynamic outcomes in patients with superficial reflux associated with primary deep axial reflux who underwent isolated superficial vein ablation without improvement. Methods: This is a retrospective study of deep venous valve anomalies in patients who underwent superficial vein ablation for superficial and associated deep reflux. A group of 21 patients who were diagnosed with saphenous reflux associated with primary deep axial reflux, were submitted to great saphenous vein ablation. In 17 patients the deep reflux was not abolished. In this subgroup, surgical exploration of the deep valve was carried out using venotomy for possible valve repair. Results: Among the 17 subgroup patients, four post-thrombotic lesions were discovered intra-operatively in four patients; they underwent different surgical procedures. In 13 of the subgroup patients, primary valve incompetence was confirmed intra-operatively. In 11 cases the leaflets were asymmetrical and in only two were they symmetrical. After valvuloplasty, deep reflux was abolished in all 13 patients. Clinical improvement was obtained in 12/13 patients (92%). It is noteworthy that abolition of deep reflux was associated with significant improvement in air plethysmography data as well as with improvement in clinical status measured on CEAP class, VCSS and the SF-36 questionnaire. Conclusion: Failure to correct deep axial reflux by superficial ablation in patients with superficial and associated primary deep axial reflux may be related to asymmetry in the leaflets of the incompetent deep venous valve.